Implication of adsorption preferences of ions and surfactants on the shape control of gold nanoparticles: a microscopic, atomistic perspective - Meena, Santosh Kumar; Meena, Chandrakala (Nanoscale, 2021)
Shape modulation of nanoparticles is crucial for their tailored applications; however, it depends on surfactants, ions, reactants, and other additives present in the growth solution. Here we dissect the role of surfactants, their counterions (halide ions), silver ions, and gold reactant in gold nanoparticle anisotropic growth using polarizable surfaces and nanoseed molecular dynamics simulation models. Our planar surface models predict a 14%-16% increment in cetyltrimethylammonium bromide (CTAB) coverage on Au(111) and Au(100) due to the surface polarization effect. The CTAB micelle adsorbs compactly similar to that observed on non-polarizable surfaces. The cetyltrimethylammonium chloride (CTAC) micelle remains in solution leaving the polarizable gold surfaces unprotected, similar to that observed with the non-polarizable surfaces, which favors isotropic growth. The cetyltrimethylammonium iodide (CTAI) micelle adsorbs with higher surface densities than CTAB on all the surfaces. The surface polarizable penta-twinned nanoseed model predicts the total surface coverage of the cetyltrimethylammonium cation (CTA(+)), Br- and Ag+ to be around two times higher on the side as compared to the tip of the nanoseed, leading to a 2.6 times higher initial rate of adsorption of AuCl2- on the tip than on the side. Predicted CTA(+) surface densities on the tip and the side of the nanoseed are consistent with experimental results. Our simulations explain the growth mechanism of anisotropic nanoparticles and the microscopic origin of their controlled shapes.

On the origin of controlled anisotropic growth of monodisperse gold nanobipyramids - Meena, Santosh Kumar; Lerouge, Frederic; Baldeck, Patrice; Andraud, Chantal; Garavelli, Marco; Parola, Stephane; Sulpizi, Marialore; Rivalta, Ivan (Nanoscale, 2021)
We elucidate the crucial role of the cetyl trimethylammonium bromide (CTAB) surfactant in the anisotropic growth mechanism of gold nano-bipyramids, nano-objects with remarkable optical properties and high tunability. Atomistic molecular dynamics simulations predict different surface coverages of the CTAB (positively charged) heads and their (bromide) counterions as function of the gold exposed surfaces. High concentration of CTAB surfactant promotes formation of gold nanograins in solution that work as precursors for the smooth anisotropic growth of more elongated nano-bipyramidal objects. Nanobipyramids feature higher index facets with respect to nanorods, allowing higher CTAB coverages that stabilize their formation and leading to narrower inter-micelles channels that smooth down their anisotropic growth. Absorption spectroscopy and scanning electron microscopy confirmed the formation of nanograins and demonstrated the importance of surfactant concentration on driving the growth towards nano-bipyramids rather than nanorods. The outcome explains the formation of the monodisperse bipyramidal nano-objects, the origin of their controlled shapes and sizes along with their remarkable stability.

Influence of van der waals interactions between the alkyl chains of surface ligands on the size and size distribution of nanocrystals prepared by the digestive ripening process - Shimpi, Jayesh R.; Thomas, Rinto; Meena, Santosh Kumar; Prasad, Bhagavatula L. V. (Langmuir, 2023)
Thermal heating of polydispersed nanocrystals (NCs) with surface-active organic ligands in a solvent leads to the formation of monodispersed NCs, and this process is known as digestive ripening (DR). Here, by performing DR on Au NCs using different-chain-length amine and thiol ligands, we evidently show that ligands with C-12 chain length result in the formation of NCs with narrow size distributions when compared to C-8, C-16, and C-20 chain length ligands. Furthermore, our findings also show that in the case of alkyl thiol, the NC size remains more or less the same, while the size distribution gets altered significantly with the chain length. On the other hand, both size and size distribution are affected significantly when the alkyl amine chain length is varied. Fourier transform infrared (FTIR) studies indicate that the van der Waals (vdW) interactions are weakest when the amine with C-12 carbon chain is used as the DR agent, while in the case of thiols, molecules with C-8 and C-12 chain lengths have nearly the same vdW interactions (with C-12 slightly weaker than C-8), which are weaker than those of C-16 and C-20. Molecular dynamics (MD) simulation results corroborate the experimental observations and suggest that due to more defects in the alkyl chain, the C-8 and C-12 (amine as well as thiol) ligands are disordered and less stable on Au(111) and Au(100) surfaces. This could result in efficient etching and redeposition, making the ligands with C-8 and C-12 chain lengths the better DR agents.

Self-assembled amino acid microstructures as biocompatible physically unclonable functions (BPUFs) for authentication of therapeutically relevant hydrogels - Akavaram, Vishwas; Kumar, Kush; Sriram, Shreya; Narra, Saisrinath; Kumawat, Akshant; Meena, Santosh Kumar; Pushpavanam, Karthik (Macromolecular Bioscience, 2023)
Counterfeited biomedical products result in significant economic losses and pose a public health hazard for over a million people yearly. Hydrogels, a class of biomedical products, are being investigated as alternatives to conventional biomedical products and are equally susceptible to counterfeiting. Here, a biocompatible, physically unclonable function (BPUF) to verify the authenticity of therapeutically relevant hydrogels are developed. The principle of BPUF relies on the self-assembly of tyrosine into fibril-like structures which are incorporated into therapeutically relevant hydrogels resulting in their random dispersion. This unclonable arrangement leads to distinctive optical micrographs captured using an optical microscope. These optical micrographs are transformed into a unique security code through cryptographic techniques which are then used to authenticate the hydrogel. The temporal stability of the BPUFs are demonstrated and additionally, exploit the dissolution propensity of the structures upon exposure to an adulterant to identify the tampering of the hydrogel. Finally, a platform to demonstrate the translational potential of this technology in validating and detecting tampering of therapeutically relevant hydrogels is developed. The potential of BPUFs to combat hydrogel counterfeiting is exemplified by its simplicity in production, ease of use, biocompatibility, and cost-effectiveness.
Keywords: anti-counterfeiting; hydrogels; physically unclonable functions; Self-assembly; translational

Investigating the design of ssPalmO-derived lipid nanoparticles for mRNA delivery applications using molecular dynamics simulations - Barange, Anjana; Luwang, Meitram Niraj; Meena, Santosh Kumar (ACS Omega, 2025)
The rational design of lipid nanoparticles (LNPs) is essential for the effective transport of drugs and genetic material, as their structural and dynamic properties are heavily influenced by lipid composition and functional group modifications. In this study, we employed molecular dynamics simulations with density functional theory (DFT) derived force fields to investigate the bilayer properties of ssPalmO lipids, their phenyl ester (ssPalmO-phe) and benzyl ester (ssPalmO-ben) derivatives, as well as their cis and trans isomers. While all systems formed stable bilayers, cis-ssPalmO deviated by adopting a flexible, nonlamellar architecture. Trans isomers of ssPalmO-phe and ssPalmO-ben exhibited greater bilayer thickness, packing density, and order parameters due to stronger intramolecular chain interactions, while their aromatic substituents reduced lateral diffusion relative to ssPalmO. Trans isomers exhibited lower electrostatic potential differences, which increased upon incorporation of helper lipids, concomitantly enhancing bilayer packing and thickness while suppressing diffusion. These results clarify how lipid functionalization, stereochemistry, and helper lipid composition modulate bilayer organization, offering molecular level guidance for rational LNP design in drug and mRNA delivery.